2019
DOI: 10.1142/s0217984919502944
|View full text |Cite
|
Sign up to set email alerts
|

Finite temperature behaviors of q-deformed Fermi gases

Abstract: During the last three decades, non-standard statistics for indistinguishable quantum particles has attracted broad attentions and research interests from many institutions. Among these new types of statistics, the qdeformed Bose and Fermi statistics, originated from the study of quantum algebra, are being applied in more and more physical systems. In this paper, we construct a q-deformed generalization of the BCS-Leggett theory for ultracold Fermi gases based on our previously constructed q-deformed BCS theory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…− on chlorinated and even fluorinated aliphatic or aromatic substrates effects ejection of a halide anion; the remaining carbon‐centred radical then abstracts a hydrogen atom when a suitable donor is present . Although such an exchange of a halogen by hydrogen is of general importance for syntheses and environmental remediation, the use of the intermediate radicals as building blocks in cross‐coupling reactions is even more interesting …”
Section: Resultsmentioning
confidence: 99%
“…− on chlorinated and even fluorinated aliphatic or aromatic substrates effects ejection of a halide anion; the remaining carbon‐centred radical then abstracts a hydrogen atom when a suitable donor is present . Although such an exchange of a halogen by hydrogen is of general importance for syntheses and environmental remediation, the use of the intermediate radicals as building blocks in cross‐coupling reactions is even more interesting …”
Section: Resultsmentioning
confidence: 99%
“…Since there are considerable research attempts and notable advancements using various metal-based materials for hydrolysis reactions, the majority of researchers focus on magnesium-based and aluminum-based compounds [12][13][14][15][16][17][18][19]. Furthermore, the current global emphasis on sustainability and environmentally friendly solutions motivates scientists to explore the utilization of waste materials as potential energy sources, in line with the principles of the circular economy.…”
Section: Introductionmentioning
confidence: 99%
“…The monodomain alignment of FLC molecules occurred in the asymmetric boundary cell without applying any voltage. The interaction between LC molecules and electromagnet wave have been investigated theoretically and experimentally [15,16] for enhancing the nonlinear optical properties of nematic LC. It is found that the interaction becomes larger when the incident intensity increases at particular pretilt angle.…”
Section: Introductionmentioning
confidence: 99%